Heterophoria in multiple sclerosis patients: a proof of principle cross-sectional study - Graf, Jonas; Weise, Margit; Guthoff, Tanja; Balloff, Carolin; Gasis, Marcia; Link, Heike; Küchlin, Sebastian; Lagrèze, Wolf; Meuth, Sven G.; Aktas, Orhan; Albrecht, Philipp (Frontiers in Immunology, 2024)
Objectives The pathophysiology of multiple sclerosis (MS) involves inflammatory neurodegeneration in the brainstem, cerebellum, and retina. The clinical relevance of oculomotor involvement in MS, however, remains uncertain. Methods In this cross-sectional study, we evaluated heterophoria as a (sub)clinical tool in 54 MS patients and 55 age-matched healthy controls (HCs). We quantified heterophoria in prism diopters for distance and near range with orthoptic examination. Our primary outcome was high degrees of horizontal heterophoria (HDHH) defined as measurements beyond ±2 standard deviations from the mean prism diopter of heterophoria of our HCs. Results More than one-third (37%, n=20/54) of MS patients but only 11% (n=6/55) of HCs were classified as HDHH [distance, MS=9% (n=5/54) versus HC=6% (n=3/55); near, MS=19% (n=10/54) versus HC=5% (n=3/55)]. Our MS patients presented more combined vertical and horizontal deviations at near range [MS 19% (n=10/54) versus for HC 7% (n=4/55)]. We observed the combination of HDHH both at distance and at near testing in 9% (n=5/54) of MS patients but not at all in HCs (n=0/55). Discussion Despite the high prevalence of heterophoria, HDHH may be an additional (sub)clinical tool of subclinical involvement in MS. Thus, orthoptic examination may be an additional tool to improve MS diagnostic procedures.